2022
DOI: 10.24235/al.ibtida.snj.v9i1.10858
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Islamic Religious Education Learning through Class Management in Elementary Schools

Abstract: This study aims to describe the planning for improving the quality of Islamic religious education learning through classroom management, the implementation of classroom management, and teachers' efforts in improving the quality of Islamic religious education learning. This study uses a qualitative approach with descriptive methods based on data collection techniques, including observation, interviews, and document analysis. The stages of data analysis include data reduction techniques, data presentation, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…This condition is in line with the research results of Helmon & Sennen (2016), which state that there are still some teachers who teach with inadequate abilities, have not prepared for learning in a well-programmed manner, and have not been able to master information technology in learning optimally (Zailani et al, 2024) Apart from that, there are teachers who have adequate academic qualifications and competencies but their performance is still low (Farihin et al, 2022). Regarding educational qualifications, MTA Surakarta High School teachers consist of 68 people: 10 people with master's degrees, 57 bachelor's degrees, and 1 person with a Diploma 3.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This condition is in line with the research results of Helmon & Sennen (2016), which state that there are still some teachers who teach with inadequate abilities, have not prepared for learning in a well-programmed manner, and have not been able to master information technology in learning optimally (Zailani et al, 2024) Apart from that, there are teachers who have adequate academic qualifications and competencies but their performance is still low (Farihin et al, 2022). Regarding educational qualifications, MTA Surakarta High School teachers consist of 68 people: 10 people with master's degrees, 57 bachelor's degrees, and 1 person with a Diploma 3.…”
Section: Introductionsupporting
confidence: 82%
“…SMA MTA Surakarta follows these standards by implementing a comprehensive curriculum and innovative teaching methods. In this way, students receive the quality education relevant to the times' needs (Farihin et al, 2022). The government also emphasizes Regulations regarding technology use in education (Permana et al, 2023).…”
Section: Jurnalmentioning
confidence: 99%
“…By making lesson plans, learning objectives will be more focused and strengthen the desired goals. Teachers will find it easier to diagnose whether the learning is on the right track or not after the course ends (Farihin et al, 2022;Husnani et al, 2020;Yamin, 2023). As we know that all learning activities are aimed at achieving a particular goal.…”
Section: Planningmentioning
confidence: 99%
“…improving the quality of learning can be done by planning everything that will be done, carrying out everything that has been planned, and evaluating the learning activities carried out. 11 In other aspects, research related to the role of the madrasa head, which is related to the theme of this research, is as follows. First, Salim concluded that the leadership of the madrasa head could not be separated from the quality of education.…”
Section: Introductionmentioning
confidence: 99%